The immediate effect of bilateral self myofascial release on the plantar surface of the feet on hamstring and lumbar spine flexibility: A pilot randomised controlled trial. Issue 3 (July 2015) - Grieve, Rob; Goodwin, Faye; Alfaki, Mostapha; Bourton, Amey-Jay; Jeffries, Caitlin; Scott, Harriet
Summary Background Self myofascial release (SMR) via a tennis ball to the plantar aspect of the foot is widely used and advocated to increase flexibility and range of movement further along the posterior muscles of a proposed "anatomy train". To date there is no evidence to support the effect of bilateral SMR on the plantar aspect of the feet to increase hamstring and lumbar spine flexibility. Aim The primary aim was to investigate the immediate effect of a single application of SMR on the plantar aspect of the foot, on hamstring and lumbar spine flexibility. The secondary aim was to evaluate the method and propose improvements in future research. Design A pilot single blind randomised control trial. Participants Twenty four healthy volunteers (8 men, 16 women; mean age 28 years ± 11.13). Method Participants underwent screening to exclude hypermobility and were randomly allocated to an intervention (SMR) or control group (no therapy). Baseline and post intervention flexibility was assessed by a sit-and-reach test (SRT). A one way between groups analysis of covariance (ANCOVA) was conducted to compare between group outcome SRT measurements. Baseline pre-intervention and control SRT measurements were used as the covariate in the analysis. Results There was a significant increase (p = 0.03) in the intervention SRT outcome measurements compared to the control group, with a large effect size. Conclusion An immediate clinical benefit of SMR on the flexibility of the hamstrings and lumbar spine was indicated and suggestions for methodological improvements may inform future research.